Tecnologias do lar e pedagogias de gênero: representações da “dona de casa ideal” na revista Casa & Jardim (anos 1950 e 1960) - Padilha, Ana Caroline de Bassi (2014)
This paper proposes to investigate the associations between domestic technologies and types of femininity in the magazine Casa & Jardim (House & Garden) as gender pedagogies media. The outline of the study focuses the discourses of textual and image about domestic technologies in the magazine Casa & Jardim during the 1950s and 1960s. In this context, the magazines aimed at female audiences sought to create an identification of women with space and domestic consumption, presenting the home technologies, especially appliances, as resources that could ensure domestic comfort, facilitating the daily routines of housewives and providing more welfare families. In this record, the household technologies both favored as charmed everyday activities. However, in parallel, the standards of cleanliness and organization of homes also become significantly more demanding. From a qualitative interpretative approach, will understand how they were configured representations of "ideal housewife" in the magazine Casa & Jardim. We point out that the discourses in the magazine of the household technologies played an important role in the generated expectations regarding the middle class modern housewife role, whose social identity was closely tied to images of wife and mother.